The Effect of Tiktok Content Type and Content Interaction on Brand Awareness of Custom Cake D’meals - Aisya Risnanda Fadhilla; Luthfiyah Nurlaela; Aulia Bayu Yushila; Ratna Palupi Nurfatimah (Universitas Negeri Padang, 2026)
This study aims to analyze the partial and simultaneous effects of TikTok content type and content interaction on the brand awareness of Custom Cake D’meals. The growing popularity of custom cakes on TikTok provides the background for examining how content strategies and audience engagement contribute to brand awareness. This research employs a quantitative explanatory approach using a survey of 95 respondents who follow the TikTok account @milaniaadrr (owner of Custom Cake D’meals). The sample was selected using purposive sampling and the Slovin formula. Data were analyzed using multiple linear regression with t-test and F-test. The results indicate that content type and content interaction influence brand awareness, and simultaneously have a significant effect with a coefficient of determination of 48.5%. These findings suggest that effective TikTok marketing strategies require alignment between appropriate content formats and efforts to encourage active audience interaction. This study provides empirical evidence for culinary business practitioners in utilizing social media to build brand awareness and supports Culinary Education by offering practical insights for developing innovative promotional strategies aligned with the modern culinary industry.